Expatriate adjustment in hotels in Dubai, UAE. Issue 3 (3rd July 2022) - Wilson, Melissa; Dutt, Christopher S.
Abstract: The article explored factors influencing the adjustment of expatriates working in hotels in Dubai. Given the high number of expatriates in Dubai and the importance in ensuring their suitable adjustment – so as to avoid an emotionally and economically damaging failed expatriate assignment – research is needed to understand what elements affect their adjustment process. This study focuses on the individual's motivation to expatriate and the type of expatriate; self-initiated, organizational, or trailing spouse. Results suggest that expatriates who chose to expatriate to improve their career or earn more adjusted better than those who expatriated to "escape" poorer conditions back home.